Pengembangan Website Katalog dan Pemesanan Online Menggunakan Metode Waterfall untuk Monitoring Penjualan - Hilmy Budiwijaya; Ratih Nindyasari; Alif Catur Murti (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Technological developments encourage businesses to adopt digital systems to improve efficiency and marketing reach. Toko ABC Store, which sells various processed aluminum products such as cupboards, display cases, and shelves, still uses manual sales and recording processes, resulting in inefficiency in transaction management and product information delivery. This study aims to design and develop a product catalog and online ordering website that enables customers to view product details and place orders online with digital payment support using Midtrans. The system was developed using the Waterfall method, PHP, and MySQL and tested using Black Box Testing. System design employed flowcharts, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), database design, and interface wireframes. The results show that the developed website successfully integrates a product catalog, online ordering, digital payment through Midtrans, inventory management, a sales monitoring dashboard, sales reports, and a price calculator. Black Box Testing of seven main features showed that all features were valid.